Deformation and failure analysis of surrounding rock mass in deep buried tunnels subjected to excavation. Issue 4 (October 2021) - Dong, Linlu; Xiao, Peiwei; Yang, Xingguo; Li, Biao; Mao, Haoyu; Xu, Nuwen
Abstract: With the rapid development of underground engineering, the construction of hydraulic tunnel is faced with complex geological conditions. Rock burst and deformation have become the bottleneck of engineering construction. The study of deformation and failure mechanisms of surrounding rock mass during the excavation of deep buried tunnel has become important for the field of underground engineering. The traffic tunnel of Shuangjiangkou hydropower station is studied to identify the failure mechanism of surrounding rock mass of deep buried tunnel. We introduced microseismic monitoring technology to delineate potential risk areas and reveal the space-time evolution of microfractures. The failure type of the surrounding rock is determined by source parameters. The relationship between surrounding rock deformation and excavation dynamic response is analyzed based on the geological and microseismic data. The results show that the 3D microseismic visualization model can realize the advanced detection of the internal damage of surrounding rock. The source parameters reveal that tensile failure is the main form of failure in the tunnel surrounding rock. Strong unloading and poor geological conditions are the main factors affecting the stability of surrounding rock mass. The study combines microseismic monitoring with field investigation, and then comprehensively evaluates the stability of the tunnel surrounding rock providing a reference for similar underground engineering.